(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The Community Law has been harmonized in Europe thanks to the Directive and the Regulation allowing companies to protect their rights filing a unique applicationin the whole territory of the European Union. The Office in charge of protecting the Community Trademark (OHIM) is located in Alicante and so far it has received more than 650. 000 CTM applications.The success of the Community trademark system proves that this model of regional protection was the right European answer to the phenomenon of the economic globalization. Likewise, it has generated other effects: on the one hand, the development of a “corpus” of new doctrine and jurisprudence, which knowledge is essential for any IP expert and, on the other hand, a substantive reduction of the cost necessaryto protect trademarks in Europe. And these factors will probably provoke the necessity of re-examining the relationships between the Community and national trademark systems.